Optimization algorithm-based approach for modeling large deflection of cantilever beam subject to tip load - Gao, Fei; Liu, Gaoyu; Wu, Xinyu; Liao, Wei-Hsin (Mechanism and machine theory, 2022)
•Optimization algorithm-based approach (OABA) is proposed to predict the large deflection of cantilever beams.•This method can predict the large deformation of uniform and non-uniform beams with high accuracy.•This method provides a new insight into the derivation of large deflection of cantilever beam.•This method can solve the deformation of compliant parallel-guiding mechanism. The modeling of beam mechanisms, especially non-uniform beams, becomes complicated due to the geometric nonlinearity that is proved to be significant with large deflection. A new method, called optimization algorithm-based approach (OABA), is proposed to predict the large deflection of uniform and non-uniform cantilever beams, in which an optimization algorithm is exploited to find the locus of the beam tip. The Euler-Bernoulli beam theory is employed here. With the derived locus of the beam tip, the deflection curve of the cantilever beam can be calculated. The optimization algorithm in this paper is embodied in a particle swarm optimization (PSO) algorithm. Experimental results show that the proposed method can precisely predict the deflection of the uniform and non-uniform cantilever beams. The maximum error is limited to 4.35% when the normalized maximum transverse deflection reaches 0.75. To demonstrate the effectiveness of this method in analyzing compliant mechanisms, we also exploited this method to predict the deformation of a compliant parallel-guiding mechanism.